The evolutionary dynamics of insecticide resistance in the whitefly, Bemisia tabaci - Jones, Christopher Mark (2011)
The whitefly Bemisia tabaci (Hempitera: Aleyrodidae), is one of most destructive insect pests of agriculture and horticulture worldwide. B. tabaci has an extensive host-plant range, transmits several plant viruses and is a highly invasive species. Managing B. tabaci is therefore extremely problematic and expensive, with a heavy burden placed upon insecticides. Despite a broad spectrum of insecticidal chemistry available for whitefly control, resistance is widespread and insecticide resistance management (IRM) programmes have been introduced to prolong the longevity and efficacy of these compounds. In particular, resistance is commonly associated with two morphologically indistinguishable and invasive populations, known as the B and Q biotypes. The identification of these biotypes using molecular-based diagnostics has become a key feature of IRM programmes. The development of a highthroughput real-time PCR assay which was able to discriminate between B and Q biotypes is described in Chapter 3 of this project. Two major mechanisms of resistance, target-site modification (i. e. pyrethroids and the sodium channel) and enzyme detoxification (i. e. P450-based metabolism of neonicotinoids) have been widely studied in resistant B and Q biotypes of B. tabaci. The evolutionary origins of two 'knockdown resistance' mutations associated with pyrethroid resistance are described in Chapter 4. Furthermore, the neonicotinoid, imidacloprid, is one of the most successful Insecticides registered for B. tabaci; however, reports of resistance are rapidly increasing. The molecular characterisation of imidacloprid resistance in B. tabaci, and in particular, the association of a P450-enzyme (CYP6CM1) with agespecific resistance, is reported in Chapter S. The advancement in our understanding of the molecular mechanisms underlying insecticide resistance is essential to improve management strategies Implemented against this pest.